Disease-resistant pigeonpeas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Wilt and sterility mosaic are two devastating diseases of pigeonpea. Wilt is caused by a fungus which blocks the water conducting tissues of plants, causing plants to wilt and then ultimately to die. Sterility mosaic prevents the formation of...